Rancang Bangun Sistem Informasi Administrasi Pelatihan Berbasis Web pada Dinas Pariwisata, Pemuda dan Olahraga Kabupaten Tanah Datar - Caisar, Ariyandra Putera; Adri, Muhammad; Irfan, Dedy; Marta, Rizkayeni (TSAQOFAH, 2025)
The manual management of athlete data at the Department of Tourism, Youth, and Sports of Tanah Datar Regency has led to various challenges, including administrative inefficiencies and difficulties for coaches in analyzing athlete performance quickly and accurately. This study aims to implement a web-based athlete management information system using the Laravel framework and the prototype method as a system development approach. System testing was conducted through black box testing using use case testing to ensure all functionalities operated according to predefined scenarios and to maintain data integrity. The test results indicate that the system achieved 100% functionality success, applied strict data validation, and effectively implemented role-based access control (RBAC) for administrators, coaches, and athletes. The system has proven to be a reliable and secure integrated solution to support athlete data management processes, improve work efficiency, and accelerate data-driven decision-making for performance enhancement. This study offers practical contributions to the digitalization of public services in the sports sector and opens avenues for further development, including real-time performance analytics integration.